Designing application of return on investment (ROI) for residential net energy metering scheme using Microsoft Visual Basic - Mohammad Radzi, Nur Hanis; Shiro, Syahirah (Penerbit UTHM, 2020)
Renewable energy is energy that is generated from natural processes that is continuously replenished. In 2011, the Renewable Energy Act has been authorized by Malaysian Government to encourage generation of energy from renewable resources. In Feed-in-Tariff (FiT) scheme, the energy generation introduced are from biogas, biomass, small hydropower and solar photovoltaic. However, commencing on 1st November 2016, a 500MW capacity under Net Energy Metering (NEM) scheme is implemented. In NEM scheme, the energy resources involved is solar ..